Therapeutic Communication Between Psychiatrists and Patients with Mental Health Disorders (Mental Illness) at Waled Hospital, Cirebon Regency - Maulana, Reza; Siswoyo, Mukarto; Wihayati, Welly (Lembaga Penelitian Universitas Swadaya Gunung Jati, 2021)
Mental health is a significant thing for life, as a primary component of mental and physical health like both sides of a coin that complement each other. If our souls experience mental health disorders (mental illness), it will affect the physical and vice versa. If it is disturbed, all the things we do will hamper, one of which is communicating with other people. This study aims to identify mental health disorders (mental illness) using therapeutic communication conducted by a psychiatrist. Research on mental health (mental illness) problems begins with knowing therapeutic communication therapy conducted by psychiatrists with patients, revealing the therapeutic communication phases, and developing a rapport when conducting therapeutic communication for patient recovery. The research uses a qualitative method in which data collection is done by interviews, observations, documentation, and literacy studies to dig deeper into existing problems. As the object of this research is a psychiatrist who has work experience to cure mental health (mental illness) in RSUD Waled Kabupaten Cirebon. In this research, it is was found that therapeutic communication is essential in the relationship phase when treatment is taking place. The type of treatment for each type of mental disorder is different. The treatment is needed to develop rapport at each meeting because it is very influential and eliminates all factors, such as insight and community stigma. Therapeutic communication is carried out through four phases: the pre-action phase, the introduction/orientation phase, the work phase, and the termination phase. Even though the same treatment phase, but the way of treatment in each type of mental disorder is different and rapport is very supportive of recovery in a psychiatrist's treatment.